2009
DOI: 10.1016/j.marenvres.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hepatic phase I and II biotransformation reactions in eight finfish species

Abstract: Hepatic microsomes and cytosols of channel catfish (Ictalurus punctatus), rainbow trout (Oncorhynchus mykiss), Atlantic salmon (Salmo salar), red tilapia (Oreochromis sp.), largemouth bass (Micropterussalmoides), striped bass (Morone saxatilis), hybrid striped bass (M. saxatilis x M. crysops), and bluegill (Lepomis macrochuris) (n=8) were used to study the kinetics of phase I (ECOD, EROD, PROD, BROD) and phase II (UDP-glucuronosyltransferase (UDPGT)-, sulfotransferase (ST)- and glutathione-s-transferase (GST)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Phase I and phase II biotransformation reactions are of great importance in the understanding of metabolism of endogenous molecules and transformation of xenobiotics and drugs in fish and other species [12]. The main enzymes that detoxify ROS in all organisms are functionally divided into antioxidant defense enzyme activities (superoxide dismutase-SOD, catalase-CAT, glutathione peroxidase-GSH-Px and glutathione reductase-GR) and biotransformation phase II components (for instance, glutathione-S-transferase-GST and reduced/oxidized glutathione) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Phase I and phase II biotransformation reactions are of great importance in the understanding of metabolism of endogenous molecules and transformation of xenobiotics and drugs in fish and other species [12]. The main enzymes that detoxify ROS in all organisms are functionally divided into antioxidant defense enzyme activities (superoxide dismutase-SOD, catalase-CAT, glutathione peroxidase-GSH-Px and glutathione reductase-GR) and biotransformation phase II components (for instance, glutathione-S-transferase-GST and reduced/oxidized glutathione) [8].…”
Section: Introductionmentioning
confidence: 99%
“…16 The induction of GST activity as for CYP450 is regulated, in part by the Ah receptor. 25 Indeed, an increase in hepatic GST activity has been reported in several studies after fish exposure to PAHs, PCBs and certain VOCs. 17,45,46 Various substrates involved in GST activity are recognized by the binding site of hydrophobic substrates.…”
Section: Dna Damage Gst Activity Lipid Peroxidation Erod Activitymentioning
confidence: 97%
“…Glutathione S-transferase is an important phase II enzyme that catalyses the conjugation of electrophilic compounds to GSH, 25 GST reacts with a wide spectrum of environmental pollutants. 26,27 It has been reported that the enzyme GST react differently to a variety of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation occurs by various mechanisms including inhibition and induction. Additionally, protein and gene expressions vary between fishspecies and sexes and are affected by diet (Celander et al, 1989;Christen and Fent, 2014;Crago and Klaper, 2011;Gonzalez et al, 2009). …”
Section: Metabolism Of Xenobiotics By Fish -Proteins and Genesmentioning
confidence: 99%